Integration of systemic and process approaches to an enterprise management within the National project “Labor productivity and employment support” - V. L. Popov; Т. V. Alexandrova (Управленческие науки)
The paper explores issues related to improving the quality of management at enterprises which are participating in the implementation of the priority national project “Labor Productivity and Employment Support”. The problem is that at the enterprises participating in the national project, ongoing changes often do not affect the fundamental foundations of improving managerial activity; a systematic and process approach to management is traditionally positioned autonomously from each other. This situation does not allow participants in the national project to realize fully the existing potential for improving labor productivity. To more effectively achieve the target parameters of this national project at the level of individual enterprises, it was proposed to integrate the basic elements of a systemic and process approach to management. A comparative analysis of the systemic and process approaches to management in relation to the participants of the national project has been completed. There were identified the main groups of management processes associated with the basic elements of the enterprise management system in the framework of the national project. Also, there was developed a model for integrating systemic and process approaches to managing the company participant to increase labor productivity. The results of the study were tested in the practice of implementing the national project “Labor Productivity and Employment Support” at large industrial companies of the Perm Territory. The research used the methodology of an integrative approach to solving management problems, as well as the methodology of system and comparative analysis. The results of the study can be used in the Federal and regional centers of competencies to develop recommendations for improving management at enterprises participating in the implementation of the national project “Labor productivity and employment support”.